(untitled) (Economic and Political Thought, 2012)
The aim of the article is to present the influence of the official speeches made by the representatives of German exiles and other politicians on the contemporary relations with the eastern neighbors of Germany, especially Poland, in the context of contemporary processes taking place in Europe. The text is mainly based on the analysis of German publications. Analyzing the fragments of speeches made by the leaders of German compatriots’ (Landsmannschaft) associations and politicians representing various political parties in that country, the author used a comparative method. The aim of organizing this kind of undertakings was to maintain the interest in and the memory of the displaced Germans among the society and politicians. The discussion about the role of the collective memory of the World War II, started by the displaced Germans, was also part of the debate before the so-called eastern enlargement of the European Union in 2004, which influenced the relations between Poland and Germany. The proof of the political character of this discussion is the fact that some of the displaced Germans tried to combine the European integration topic with the problems left over from the previous era of relations with the eastern neighbors. The best example is the participation of Hans Gert Pöttering, the then President of the European Parliament, in Days of Homeland (Tag der Heimat), who spoke about the issue of damages claims in the contemporary relations between Poland and Germany. The use of historical events in politics also took place in the first decade of the 21st century and was an attempt to divert attention from current issues on both sides of the Odra as well as in other countries of the region.